2023
DOI: 10.3390/cancers15112975
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Receptor Radionuclide Therapy (PRRT): Innovations and Improvements

Abstract: Neuroendocrine neoplasms (NENs) are tumors originating from neuroendocrine cells distributed throughout the human body. With an increasing incidence over the past few decades, they represent a highly heterogeneous group of neoplasms, mostly expressing somatostatin receptors (SSTRs) on their cell surface. Peptide receptor radionuclide therapy (PRRT) has emerged as a crucial strategy for treating advanced, unresectable neuroendocrine tumors by administering radiolabeled somatostatin analogs intravenously to targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The NETTER 1 study demonstrated the significant benefits of PRRT in GEP-NETs and introduced the potential for therapeutic effects in neuroendocrine tumors [ 2 ]. The ability to target lesions due to somatostatin receptor expression offers the potential for targeted treatment of multiple foci, whereas the effect of treatment on adjacent clones within the lesion via the cross-fire effect may help treat heterogeneous metastatic foci [ 51 ]. However, it should be noted that this study did not include LNETs and its efficacy in these tumors has not been confirmed.…”
Section: Navigating Therapeutic Strategies: Efficacy In Treating Lung...mentioning
confidence: 99%
“…The NETTER 1 study demonstrated the significant benefits of PRRT in GEP-NETs and introduced the potential for therapeutic effects in neuroendocrine tumors [ 2 ]. The ability to target lesions due to somatostatin receptor expression offers the potential for targeted treatment of multiple foci, whereas the effect of treatment on adjacent clones within the lesion via the cross-fire effect may help treat heterogeneous metastatic foci [ 51 ]. However, it should be noted that this study did not include LNETs and its efficacy in these tumors has not been confirmed.…”
Section: Navigating Therapeutic Strategies: Efficacy In Treating Lung...mentioning
confidence: 99%
“…THPs are also used for peptide receptor radionuclide therapy (PRRT), which combines a tumor-homing peptide with a radionuclide or radioactive isotope as the therapeutic substance [ 167 ]. Cholecystokinin (CCK) receptors bind to gastrin, a 33 amino acid peptide hormone, and CCK2 receptor is abundant in tumors [ 168 ].…”
Section: Peptide-based Approaches For Cancer Treatmentmentioning
confidence: 99%
“…Recent advancements in biopharmaceutical engineering have resulted in the development of various drugs based on peptides or proteins [ 7 , 167 , 194 , 208 , 209 ]. The route of drug administration significantly affects its effectiveness as a treatment [ 210 , 211 ].…”
Section: Peptides In Applicationsmentioning
confidence: 99%
“…Peptide receptor radionuclide therapy (PRRT) selectively attacks tumor cells by binding to peptides expressed on their surface [ 8 ]. NETs frequently express membrane-localized somatostatin receptors (SSTRs), making these receptors suitable targets for PRRT using somatostatin analogs (SSAs).…”
Section: Introductionmentioning
confidence: 99%